Cochlear implantation in vestibular schwannoma: A game changer? A narrative review - Luis Lassaletta; Miryam Calvino; Isabel Sánchez-Cuadrado; José Manuel Morales-Puebla; Javier Gavilán (Brazilian Journal of Otorhinolaryngology)
Objectives: In recent years, indications for Cochlear Implants (CIs) have been on the rise, with Vestibular Schwannoma (VS) patients among these emerging indications. On the other hand, there is growing evidence in favor of the 'wait and see' approach as opposed to surgery or irradiation for most small VS. The aim of this paper is to discuss the current role of CIs in patients with VS, addressing the most controversial topics such as the variability of outcomes, the emerging clinical scenarios, the lack of consistent prognostic factors, and the need for an intraoperative tool to aid decision-making in challenging cases. Methods: A Pubmed search was performed, with a selection of relevant citations, and critical appraisal of selected studies. Articles written in English on VS and cochlear implantation were eligible for inclusion. Pictures of illustrative cases from a tertiary center were included. Results: The discussed topics were the following: (1) Variability in audiological outcomes; (2) Prognostic factors including tumor size, preoperative hearing, previous irradiation, extent of resection, and Neurofibromatosis type II (NF2) status; (3) Postoperative imaging; (4) The role of intraoperative testing; and (5) The current indication of CIs in different clinical scenarios. Conclusions: CIs have become a useful solution for certain patients with VS. Audiological outcomes are variable, but worse than those of conventional CI candidates. Small and medium-sized tumors and those with a better preoperative hearing are more likely to benefit from a CI. The effect of irradiation is uncertain. Outcomes in NF2 patients may decrease in the long term. The auditory nerve test system is a useful intraoperative tool in most scenarios. The variability of the outcomes still precludes routine CI in VS with normal contralateral hearing. In addition to VS undergoing surgical resection and CI placement, some observed and irradiated VS cases also benefit from a CI. Level of evidence: 5.